KUALITAS PELAYANAN TRANSPORTASI LAUT DALAM UPAYA MENINGKATKAN KEPUASAN PENGGUNA JASA LAYANAN PENYEBERANGAN TOROBULU-TAMPO (STUDY PADA PELABUHAN FERRY TOROBULU) - Muis, Amalia; Banga, Wempy; Liwaul, Liwaul (REZ PUBLICA, 2020)
This type of research is to use a qualitative descriptive approach. Data collection techniques carried out with library research, field studies, include: Interviews, Observation, and documentation. Â The results showed that the Quality of Service to the Satisfaction of Sea Transportation Service Users at the Torobulu Ferry Port was measured from the four indicators of service quality, namely simplicity, clarity and certainty, as well as the economic and equitable fairness provided by the officers from which the indicators were quite good but the simplicity indicators at the ASDP counters as well as indicators of clarity and certainty to the accuracy of the ship's trip schedule still need to be improved so that the quality provided can give satisfaction to service users as measured through the three indicators in order to create a sense of expectation that is not yet effective and needs to be optimized, visiting people back quite well, and recommend the torobulu ferry port services that still need to be optimized.